EDUX: EDucation with an aUthoring tool using XML - Mohamed Hussain, Helmi; Hussin, Aida Liza; Ahmad, Khairul Adilah; Abdul Rahman, Mazlyda; Yahaya, Rohaya; Md. Kassim, Siti Salmah (2001)
EDUX (EDucation with an aUthoring tool using XML) is an e-learning system using the intelligent hypertexts language; Extensible Markup Language (XML). EDUX enable students to follow courses at their own pace, based on their ability. EDUX is designed as an adaptable e-learning environment, which can meet the needs of the individual student. It has the intelligent agent features where for each and every student the system will generate different type of layout or presentation, based on their understanding on the subject or course. The learning process comprises of two main components: an instructor component and a student component. Instructors will be provided with a tool that has functionality for the creation of course. Students will also have a tool with three integrated functionalities for the collaborative curriculum. EDUX acts as a portal with customize web page for the instructors and students.